2004
DOI: 10.4049/jimmunol.172.2.1177
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Signaling Lymphocytic Activation Molecule- Associated Protein Interrupts IFN-γ Production in Human Tuberculosis

Abstract: Production of the Th1 cytokine IFN-γ by T cells is considered crucial for immunity against Mycobacterium tuberculosis infection. We evaluated IFN-γ production in tuberculosis in the context of signaling molecules known to regulate Th1 cytokines. Two populations of patients who have active tuberculosis were identified, based on their T cell responses to the bacterium. High responder tuberculosis patients displayed significant M. tuberculosis-dependent T cell proliferation and IFN-γ production, whereas low respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
121
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(143 citation statements)
references
References 27 publications
20
121
2
Order By: Relevance
“…1A). These data, indicating that the expression of SAP is lowest in the group of patients who displayed high immune responses to M. leprae, that is Th1-type immune responses, are in accord with our findings in tuberculosis (15) and suggest that the expression of SAP interferes with Th1 responses during mycobacterial infection.…”
Section: Expression Of Sap In Leprosy Patients Correlates With Increasupporting
confidence: 80%
See 4 more Smart Citations
“…1A). These data, indicating that the expression of SAP is lowest in the group of patients who displayed high immune responses to M. leprae, that is Th1-type immune responses, are in accord with our findings in tuberculosis (15) and suggest that the expression of SAP interferes with Th1 responses during mycobacterial infection.…”
Section: Expression Of Sap In Leprosy Patients Correlates With Increasupporting
confidence: 80%
“…Because signaling through the costimulatory molecule SLAM enhanced IFN-␥ production in leprosy patients (14), we investigated at the molecular level the alternative pathway triggered by SLAM that leads to IFN-␥ production in human leprosy. The existence of an inverse relationship between SAP expression and IFN-␥ production by Ag-stimulated T cells in tuberculosis and XLP patients (15) indicates that SAP attenuates Th1 immune responses (7,15). In fact, we showed that SAP turns off IFN-␥ production in L-Lep patients, but stimulation with SLAM and TCR together decreased SAP expression in unresponsive patients.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations